Pembentukan Karakter Islami Anak Usia Dini: Tinjauan Peran Pendidik - Aliyatuz Zulfa, Nadia; Sutrisno, Sutrisno; Sari, Nurita (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Trunojoyo Madura, 2024)
This study explores the role of educators in instilling Islamic character in early childhood through the habituation of daily prayer memorization. The main issue identified is the lack of structured Islamic character education and the minimal habituation of daily prayers as part of moral education. This is often due to a lack of understanding and effective strategies from educators in applying Islamic character education. The aim of this research is to examine the role of educators in shaping Islamic character in young children through the habituation of daily prayer memorization and to explain how this practice can be applied based on the teachings of the Qur'an and Hadith. A phenomenological approach was used, with data collection techniques including observation, interviews, and documentation. Primary data was sourced from the Qur'an, Hadith, and supporting materials such as journals, books, and articles. The research findings indicate that Islamic character education aims to develop children with Qur'anic morals and good habits in their daily lives. The habituation of daily prayers, such as those taught by the Prophets, can be incorporated into daily routines with the guidance of educators. The role of the educator is crucial, including gathering the prayers to be memorized, providing explanations, setting a good example, and motivating children who struggle with memorization. Furthermore, educators collaborate with parents to ensure the continued practice of daily prayers at home. The implications of this study emphasize the importance of Islamic character education through daily prayer memorization as a foundation for moral development in early childhood and encourage educational institutions to integrate Islamic character education into their curricula to shape a Qur'anic character in future generations.